2021
DOI: 10.1111/ppc.12813
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the relationship between social support levels and treatment compliance of individuals diagnosed with schizophrenia

Abstract: Purpose The aim of this study was to determine the relationship between social support levels and treatment compliance of individuals with schizophrenia. Design and Methods A descriptive and correlational research design was used in the study. The sample was not selected from the universe and the study was completed with 110 patients. Findings There was a significant positive correlation between the total score of family subscale and total score of the Morisky compliance scale (p < 0.05). Morisky adherence sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The support encourages them to adhere to treatment and maintain a new lifestyle. This finding has been supported by Świątoniowska‐Lonc et al ( 2021 ) in diabetic patients, Pan et al ( 2021 ) in patients with hypertension, and Altun et al ( 2022 ) in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 54%
“…The support encourages them to adhere to treatment and maintain a new lifestyle. This finding has been supported by Świątoniowska‐Lonc et al ( 2021 ) in diabetic patients, Pan et al ( 2021 ) in patients with hypertension, and Altun et al ( 2022 ) in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 54%
“…The study by Mairs et al. (2011) included family members and care providers throughout the program, and this should be a consideration for future research, as family social support is known to improve treatment outcomes ( Jameel et al., 2020 ; Jana et al., 2014 ; Ö et al., 2022 ). Other considerations may include the importance of patient preferences in decisions about the setting for the delivery of treatment and the overall acceptability of behavioural activation for people with schizophrenia and negative symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Tham et al (2018), on 92 people reported that medication adherence rate of 52 patients was low. Şahin Altun et al (2021) determined that adherence with the treatment was poor in the majority of individuals with schizophrenia. The study by Kikkert & Dekker (2017), reported that noncompliance with drug treatment is common in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%